2016
DOI: 10.1590/1807-3107bor-2016.vol30.0099
|View full text |Cite
|
Sign up to set email alerts
|

Experimental osteonecrosis: development of a model in rodents administered alendronate

Abstract: Abstract:The main objective of this study was to cause bisphosphonate-related osteonecrosis of the jaws to develop in a rodent model. Adult male Holtzman rats were assigned to one of two experimental groups to receive alendronate (AL; 1 mg/kg/week; n = 6) or saline solution (CTL; n = 6). After 60 days of drug therapy, all animals were subjected to first lower molar extraction, and 28 days later, animals were euthanized. All rats treated with alendronate developed osteonecrosis, presenting as ulcers and necroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…After reading the titles, 63 articles remained, and after careful abstract assessement, 44 reports were excluded (Table 2) due to the following reasons: reports that did not have a pure alendronane group; and studies that did not perform tooth extraction. The full text of the remaining 19 studies was retrieved 10,11,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and included in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading the titles, 63 articles remained, and after careful abstract assessement, 44 reports were excluded (Table 2) due to the following reasons: reports that did not have a pure alendronane group; and studies that did not perform tooth extraction. The full text of the remaining 19 studies was retrieved 10,11,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and included in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…In summary, from the 19 eligible studies, five 39,42,45,[52][53] were considered to have "low' risk of bias in the SYRCLE's RoB tool, three studies 40,43,49 were considered to have "unclear" risk of bias, and 11 studies were considered to have "high" risk of bias. 10,11,37,38,41,44,[46][47][48]50,51 Twelve studies reported the randomization process for group allocation, but the sequence generation and the allocation concealment were not described in any of them. 11,37,39,40,42,44,45,[47][48][49][52][53] In five 39,42,45,[52][53] studies, the authors described the characteristics of the animals in sufficient detail to consider the experimental groups to be similar at baseline and to judge the study as having "low"' risk of bias.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 3 more Smart Citations